Online komunikační strategie fakulty - Šimíčková, Klára (Vysoké učení technické v Brně. Fakulta podnikatelská, 2017)
Tato diplomová práce je zaměřená na analýzu stávajícího stavu online komunikace fakulty a na formulaci návrhů na opatření, která povedou k posílení strategického využití online nástrojů v komunikaci vysokoškolské vzdělávací instituce.

This diploma thesis is focused on an analysis of the current state of online communication of faculty and formulation of the measures which are needed for strengthening of strategical use of online communication channels within the university.
Online Communication Strategy of Faculty
Keywords: Strategie; online strategie; komunikace; online komunikace; komunikace vysokoškolské vzdělávací instituce; konkurenceschopnost; Strategy; online strategy; communication; online communication; communication of university; competitiveness